Safety and benefits of interventions to increase folate status in malaria‐endemic areas. (29th March 2017) - Verhoef, Hans; Veenemans, Jacobien; Mwangi, Martin N.; Prentice, Andrew M.
Summary: For decades, folic acid has routinely been given to prevent or treat anaemia in children, pregnant women and people with sickle cell disease. However, there is no conclusive evidence that folate deficiency anaemia constitutes a public health problem in any of these groups. Industrial flour fortification is recommended and implemented in many countries to combat neural tube defects. Dietary folates or folic acid can antagonise the action of antifolate drugs that play a critical role in the prevention and treatment of malaria. Randomised trials have shown that folic acid supplementation increases the rate of treatment failures with sulfadoxine‐pyrimethamine. The efficacy of antifolate drugs against Plasmodium is maximized in the absence of exogenous folic acid, suggesting that there is no safe minimum dose of ingested folic acid. We here review the safety and benefits of interventions to increase folate status in malaria‐endemic countries. We conclude that formal cost‐benefit analyses are required.